"Who Am I and Why Am I Here?" A Scoping Review Exploring the Templates and Protocols That Direct Actors in Their Roles as Simulated (Standardized) Patients. Issue 3 (June 2021) - Davies, Ellen L.; Pelentsov, Lemuel J.; Montagu, Adam; Gordon, Andrea L.; Hooper, Kenneth J.; Esterman, Adrian J.
Abstract : Summary Statement: Simulated patients (SPs) are increasingly used in health education and research. The aim of this article was to investigate templates and protocols that enable SPs to accurately and consistently adopt these roles. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews guided the search strategy for articles that detailed such templates or protocols. Embase Classic + Embase, ProQuest ERIC, Ovid MEDLINE, Ovid EMCare, psycINFO, and Scopus were searched, and 17 articles were included in the review. The templates and protocols that were located differed in structure, length, and depth and were developed or used in medical, nursing, allied health, and veterinary medicine disciplines. The validity, reliability, and replicability of studies are explored, and the quality of reporting is evaluated using the Simulation Research Rubric. Recommendations for increasing the rigor of programs and the reporting of research where SPs are adopted are considered. Abstract : Supplemental digital content is available in the text.